Global Existence and Blow-Up for the Classical Solutions of the Long-Short Wave Equations with Viscosity - Jincheng Shi; Shengzhong Xiao (Discrete Dynamics in Nature and Society)
We are concerned with the global existence of classical solutions for a general model of viscosity long-short wave equations. Under suitable initial conditions, the existence of the global classical solutions for the viscosity long-short wave equations is proved. If it does not exist globally, the life span which is the largest time where the solutions exist is also obtained.